Durability of Vaccine-Induced Immunity Against Tetanus and Diphtheria Toxins: A Cross-sectional Analysis - Hammarlund, Erika; Thomas, Archana; Poore, Elizabeth A.; Amanna, Ian J.; Rynko, Abby E.; Mori, Motomi; Chen, Zunqiu; Slifka, Mark K. (Clinical infectious diseases, 2016)
Background. Many adult immunization schedules recommend that tetanus and diphtheria vaccination be performed every 10 years. In light of current epidemiological trends of disease incidence and rates of vaccine-associated adverse events, the 10-year revaccination schedule has come into question. Methods. We performed cross-sectional analysis of serum antibody titers in 546 adult subjects stratified by age or sex. All serological results were converted to international units after calibration with international serum standards. Results. Approximately 97% of the population was seropositive to tetanus and diphtheria as defined by a protective serum antibody titer of ≥0.01 IU/mL. Mean antibody titers were 3.6 and 0.35 IU/mL against tetanus and diphtheria, respectively. Antibody responses to tetanus declined with an estimated half-life of 14 years (95% confidence interval, 11–17 years), whereas antibody responses to diphtheria were more long-lived and declined with an estimated half-life of 27 years (18–51 years). Mathematical models combining antibody magnitude and duration predict that 95% of the population will remain protected against tetanus and diphtheria for ≥30 years without requiring further booster vaccination. Conclusions. These studies demonstrate that durable levels of protective antitoxin immunity exist in the majority of vaccinated individuals. Together, this suggests that it may no longer be necessary to administer booster vaccinations every 10 years and that the current adult vaccination schedule for tetanus and diphtheria should be revisited.